PERAN JUMANTIK PADA KEJADIAN DEMAM BERDARAH DENGUE: STUDI POTONG LINTANG DI UPTD PUSKESMAS KUTA SELATAN - ni putu eka sukayuni; IGAA Sherlyna Prihandhani; I Wayan Artana (Jurnal Ilmu Keperawatan Komunitas, 2021)
ABSTRACTJumantik plays a role in the early vigilance system to monitor the presence and inhibit the development of the Dengue Hemorrhagic Fever (Dengue) mosquito vector. Jumantik cadres are expected to be active in monitoring their environment to reduce the number of dengue cases. However, in 2020 there will be an increase in dengue cases in South Kuta. This study purposed to determine the correlation between the role of jumantik and the incidence of dengue fever at the UPTD Puskesmas Kuta Selatan. This study used observational quantitative research with a cross-sectional design. The sample amounted to 67 jumantik selected by total sampling. Data were collected using a questionnaire and documentary sheet of DHF case reports. Data analysis used Rank Spearman's test. It was found that the majority of jumantik's role was good (77.6%) and the incidence of dengue fever decreased (74.6%). The analysis shows that there is a significant relationship between the role of jumantik and the incidence of dengue fever in the UPTD Puskesmas Kuta Selatan with a moderate and positive correlation, which means the better the role of jumantik in carrying out their duties. The better the jumantik work, the incidence of dengue fever decreases (p value 0.002 <α 0.05 and coefficient correlation of 0, 427). It is recommended to the health office to carry out training and health education for jumantik on an ongoing basis which is carried out every one semester.